Isomorfismo e gerenciamento de impressões em mecanismos de compliance : uma análise em bancos com controle público listados na B3 - Souza, Thiago Roozevelt de (2024)
The adoption of laws such as Anti-Corruption Law and State-Owned Companies Law had a clear impact on the governance of Brazilian state-owned companies, through the improvement of compliance mechanisms, which deal with aspects of integrity, ethics and combating corruption. The process of adapting to new legislation by companies in the same economic sector and with government control can lead to behavior in which companies adopt practices similar to other organizations that are already, in some way, adapted to the environment. In this way, the project aims to understand how isomorphic mechanisms contributed to the construction of compliance mechanisms in state-owned banks listed on B3, and the research method adopted will be a qualitative research, which will use a documentary analysis. The results indicate that banks show great similarity in the implementation of integrity policies and that there is strong evidence regarding the implementation of impression management practices, given that the communication and public image strategies adopted by organizations are shaped by the intersection between the institutional and stakeholder demands